Inadequate Functional Health Literacy in Spanish as a Barrier to Cervical Cancer Screening Among Immigrant Latinas in New York City - Samantha Garbers; Mary Ann Chiasson (Centers for Disease Control and Prevention, 2004)
Objective The objective of this study was to examine the association between inadequate functional health literacy in Spanish among low-income Latinas aged 40 and older and cervical cancer screening knowledge and behavior. Methods Spanish-speaking Latinas aged 4078 of various nationalities (n = 205) participated in a study that included a survey on cervical cancer knowledge and behavior administered in Spanish and the Spanish version of the Test of Functional Health Literacy in Adults. Results Compared to those with adequate and marginal health literacy, women with inadequate functional health literacy in Spanish were significantly less likely to have ever had a Papanicolaou (Pap) test (odds ratio, 0.12; 95% confidence interval [CI], 0.04-0.37) or in the last three years (odds ratio, 0.35; 95% CI, 0.18-0.68) and were significantly more likely to have had their last Pap test at a local public hospital (odds ratio, 2.43; 95% CI, 1.18-4.97). Even when controlling for other factors, women with inadequate health literacy were 16.7 times less likely (adjusted odds ratio, 0.06; 95% CI, 0.01-0.55) to have ever had a Pap test. Conclusion Almost half of the population we studied will have difficulty interpreting written medical materials, even in Spanish. When developing efforts to reach women who have not been screened, programs and service providers need to be aware that the women most in need of information about screening may be more likely to be unable to read any written materials provided to them, regardless of the language or level of simplicity of the materials. Programs and strategies need to be implemented to increase screening prevalence and to minimize the identified gaps in regular screening for Latinas who have low health literacy.